DESIVAST: Catalogs of Low-redshift Voids Using Data from the DESI Data Release 1 Bright Galaxy Survey - Hernan Rincon; Segev Benzvi; Kelly Douglass; Dahlia Veyrat; Jessica Nicole Aguilar; Steven Ahlen; Davide Bianchi; David Brooks; Todd Claybaugh; Shaun Cole; Axel de la Macorra; Peter Doel; et al. (The Astrophysical Journal)
We present three separate void catalogs created using a volume-limited sample of the DESI Data Release 1 Bright Galaxy Survey. We use the algorithms VoidFinder and V ^2 to construct void catalogs out to a redshift of z = 0.24. Excluding voids affected by the boundaries of the survey, we obtain 1489 voids with VoidFinder, 389 with V ^2 using REVOLVER pruning, and 297 with V ^2 using VIDE pruning. Comparing our catalogs with overlapping Sloan Digital Sky Survey void catalogs, we find generally consistent void properties but significant differences in the void volume overlap, which we attribute to differences in the galaxy selection and survey masks. These catalogs are suitable for studying the variation in galaxy properties with cosmic environment and for cosmological studies.